Respuesta :

Answer:

x = -4

y = -1

Step-by-step explanation:

-2x - 9 = -5x - 21

3x - 9 = -21

3x = -12

x = -4

y = -2(-4) - 9

y = 8 - 9

y = -1

Answer:

x=−4 and y=−1

Step-by-step explanation:

I will solve your system by substitution.

y=−2x−9;y=−5x−21

Step: Solve y=−2x−9for y:

Step: Substitute−2x−9foryiny=−5x−21:

y=−5x−21

−2x−9=−5x−21

−2x−9+5x=−5x−21+5x(Add 5x to both sides)

3x−9=−21

3x−9+9=−21+9(Add 9 to both sides)

3x=−12

(Divide both sides by 3)

x=−4

Step: Substitute−4forxiny=−2x−9:

y=−2x−9

y=(−2)(−4)−9

y=−1(Simplify both sides of the equation)

Answer:

x=−4 and y=−1